IS MAN A SLAVE OF DESTINY OR ITS MASTER? (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article explores in depth the relationship between human agency (free will) and destiny (determinism), drawing upon philosophical, scientific, and literary sources, as well as the ideas of numerous scholars and thinkers. The study examines the concepts of “qazo and qadar” in Islamic philosophy (Ash‘ari, Maturidi, al-Ghazali, Ibn Sina), the notion of destiny in Alisher Navoi’s works, Benjamin Libet’s neuroscientific experiment and its critiques, as well as findings from psychology and genetics, and the tragic conflict presented in Sophocles’ Oedipus Rex. In addition, the views of philosophers and scientists such as Daniel Dennett, Robert Sapolsky, Baruch Spinoza, and David Hume are analyzed. The results indicate that a human being is not merely a slave of destiny but can be its active participant and even its master—this is realized through the complex interaction of free will and determinism.
Keywords: destiny, free will, neurobiology, philosophy, determinism, “qazo and qadar”, Libet experiment, Oedipus, compatibilism.